Genetic manipulation of a metabolic enzyme and a transcriptional regulator increasing succinate excretion from unicellular cyanobacterium - Osanai, Takashi; Shirai, Tomokazu; Iijima, Hiroko; Nakaya, Yuka; Okamoto, Mami; Kondo, Akihiko; Hirai, Masami Y. (Frontiers in Microbiology, 2015)
Succinate is a building block compound that the U.S. Department of Energy has declared as important in biorefineries, and it is widely used as a commodity chemical. Here, we identified the two genes increasing succinate production of the unicellular cyanobacterium Synechocystis sp. PCC 6803. Succinate was excreted under dark, anaerobic conditions, and its production level increased by knocking out ackA, which encodes an acetate kinase, and by overexpressing sigE, which encodes an RNA polymerase sigma factor. Glycogen catabolism and organic acid biosynthesis were enhanced in the mutant lacking ackA and overexpressing sigE, leading to an increase in succinate production reaching 5 times of the wild-type levels. Our genetic and metabolomic analyses thus demonstrated the effect of genetic manipulation of a metabolic enzyme and a transcriptional regulator on succinate excretion from this cyanobacterium with the data based on metabolomic technique.